Ferroelectric hysteresis properties of 0-3 lead-free barium zirconate titanate-portland cement composites - Potong R. (2014)
Cement-based 0-3 type lead-free piezoelectric composites, made from barium zirconate titanate (BZT) ceramic particles and Portland cement (PC) are developed for smart or intelligent structure in civil engineering. Ferroelectric hysteresis properties of the composites with different BZT contents at 40-70% by volume were then investigated. The results showed that the ferroelectric hysteresis loops can be seen for all composites. The apparent remnant polarization (Pr) was found to increase with increasing BZT content. The apparent coercive field (Ec) was found to decrease with increasing BZT content from 11.0 to 7.30C/cm 2 at 15kV/cm when BZT volume content used was 40% and 70% respectively. © 2012 Copyright Taylor and Francis Group, LLC.